2014
DOI: 10.3131/jvsj2.57.102
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study of Ligand Effects on the Electronic Structures of Ligated Zinc Porphyrin using Density Functional Theory

Abstract: We study the ligand eŠect on the LUMO/HOMO of ligated zinc porphyrin (ZnP) by utilizing DFT. The ligated ZnPs are zinc meso-tetraphenylporhyrin (ZnTPP), zinc tetrabenzoporphyrin (ZnTBP), zinc meso-tetraphenyltetrabenzoporphyrin (ZnTPTBP) andˆve-coordination ZnTPP with imidazole (ZnTPP(Im)). The ligands decrease LUMO-HOMO energy gap (DE  ) of ligated ZnPs with respect to non-ligated ZnP, which is in good agreement with experiments. LUMO of ZnTPP and ZnTBP is stabilized by LUMO+1 (b 1 -type, C 2v -symmetry) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The calculated energy band gap for Zn II ‐porphyrin was 3 eV, which indicates a visible light absorption and promising potential photovoltaic properties that could be applied in the design of solar cells. The energy gap is in accordance with results recently reported for Zn II ‐porphyrin species . Together with the molecular orbital structure and the calculated energy level, it can be found that, after modification at both meso ‐and β‐positions with aryl thioacetate‐functionalised side groups and hexyl chains, respectively, the areas of high electron‐density were moved from the macrocyclic ring (shown in HOMO) to meso ‐ (as shown in LUMO) and β‐positions (as shown in LUMO+1).…”
Section: Resultssupporting
confidence: 90%
“…The calculated energy band gap for Zn II ‐porphyrin was 3 eV, which indicates a visible light absorption and promising potential photovoltaic properties that could be applied in the design of solar cells. The energy gap is in accordance with results recently reported for Zn II ‐porphyrin species . Together with the molecular orbital structure and the calculated energy level, it can be found that, after modification at both meso ‐and β‐positions with aryl thioacetate‐functionalised side groups and hexyl chains, respectively, the areas of high electron‐density were moved from the macrocyclic ring (shown in HOMO) to meso ‐ (as shown in LUMO) and β‐positions (as shown in LUMO+1).…”
Section: Resultssupporting
confidence: 90%
“…For the exchange-correlation functional, we employ B3LYP [31] and CAM-B3LYP [32] which have been integrated into the software as well. The former has provided good prediction in our previous studies on molecular orbital interaction problems [33], [34], [35], [36], excitation in solvent problems [37], [38], and reaction path coordinate to calculate the tunneling probability [39], [40], [41]. Meanwhile, the latter is needed to consider the correction of the long-range interaction in states 1a , 1b , and 1c .…”
Section: Methodsmentioning
confidence: 99%
“…Our previous works 10,27) suggest that HOMO-HOMO¹1 energy difference of ligated ZnPs [ZnTPP, ZnTBP, zinc tetraphenyltetrabenzoporphyrin or ZnTPTBP, and ZnTPP with axial imidazole ligand or ZnTPP(Im)] that are calculated by DFT are wider than non-ligated one. While in non-ligated ZnP these two orbital has 0.04 eV energy difference, in ZnTPP it is 0.19 eV, and it is wider than ZnTBP, ZnTPTBP and ZnP(Im).…”
Section: 1mentioning
confidence: 99%
“…In addition, the frontier orbital ordering is similar to non-ligated ZnP. 10) Therefore we can use the electronic structure of non-ligated ZnP as a comparison for the electronic structure of ZnTPP. And third, ZnTPP is experimentally well studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation